2014
DOI: 10.1016/j.ccell.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of De Novo NAD + Synthesis by Oncogenic URI Causes Liver Tumorigenesis through DNA Damage

Abstract: Molecular mechanisms responsible for hepatocellular carcinoma (HCC) remain largely unknown. Using genetically engineered mouse models, we show that hepatocyte-specific expression of unconventional prefoldin RPB5 interactor (URI) leads to a multistep process of HCC development, whereas its genetic reduction in hepatocytes protects against diethylnitrosamine (DEN)-induced HCC. URI inhibits aryl hydrocarbon (AhR)- and estrogen receptor (ER)-mediated transcription of enzymes implicated in L-tryptophan/kynurenine/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
228
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(242 citation statements)
references
References 45 publications
8
228
1
1
Order By: Relevance
“…We could demonstrate that during early stage NAFLD, NAD salvage via NAMPT is upregulated in mice [17], whereas in later disease stages, NAMPT and NAD levels were reported to be downregulated (reviewed in [5]). Low NAD levels may then reduce the activity of PARP-1, thereby impairing genomic integrity as was described by Tummala et al [16].…”
Section: Boosting Nad Levels In Hccmentioning
confidence: 99%
See 2 more Smart Citations
“…We could demonstrate that during early stage NAFLD, NAD salvage via NAMPT is upregulated in mice [17], whereas in later disease stages, NAMPT and NAD levels were reported to be downregulated (reviewed in [5]). Low NAD levels may then reduce the activity of PARP-1, thereby impairing genomic integrity as was described by Tummala et al [16].…”
Section: Boosting Nad Levels In Hccmentioning
confidence: 99%
“…Expression of unconventional prefoldin RBP5 interactor in hepatocytes was shown to reduce the expression of enzymes of de novo NAD biosynthesis. The resulting NAD depletion induced DNA damage by inhibiting the NAD-dependent DNA repair enzyme PARP-1, subsequent genotoxic stress, apoptosis, and compensatory proliferation leading to the development of liver tumors in mice [16]. HCC development was blocked by the restoration of hepatocellular NAD pools by supplementing nicotinamide ribose, a precursor of NAD biosynthesis [16].…”
Section: Boosting Nad Levels In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature has reported that NR will elevate NAD + levels to promote mitochondrial health and protect against metabolic disease (233)(234)(235)(236)(237). Some reports have indirectly linked NR to oxidative stress response and DNA damage repair pathways in diseased mouse models (238,239). However, the role of NR delivery in these pathways remains unclear.…”
Section: Nicotinamide Riboside Supplementationmentioning
confidence: 99%
“…Additionally, NR delivery has been reported to prevent DNA damage and tumor formation in a model of mouse hepatocellular carcinoma (239). However, the direct effects of NR on DNA damage repair have yet to be explored.…”
Section: Nicotinamide Riboside Supplementationmentioning
confidence: 99%